Implications of Climate Change on Agriculture Sector of Pakistan - Amjad, Athar Ismail (Journal of Public Policy Practitioners, 2023)
Climate change is a significant phenomenon with socio-economic effects that concern experts. Pakistan, with its diverse geographical features, is particularly vulnerable to such climate changes. Its long latitudinal area covers almost 5000 glaciers in the northern areas, which remain frozen and provide water throughout the year. The melting glaciers in northern areas and rainfall from the Arabian Sea play vital roles in water supply, agriculture, and energy production. However, Pakistan ranks at number 7 in the Global Climate Risk Index of 2017 which lists Pakistan as the most vulnerable country to climate change. It faces grave threats due to climate change and perhaps it is at the crossroads of climate change effects. These risks are further aggravated by high rates of nutrition and food insecurity. Due to changes in climatic conditions, weather becomes more erratic, resulting in severe climatic disasters which ultimately lead to food insecurity in Pakistan. It is estimated that climate changes affect every facet of food security in Pakistan, that is, its availability, access to food, utilization, and stability. Resultantly, Pakistan’s agriculture sector suffers considerably, exposing the country to critical economical, developmental, and social challenges that wreak great havoc on mankind and plant lives. The current study explored the correlation between climate changes and its effects on agricultural production in Pakistan.